A Fluorescence‐Lifetime‐Based Binding Assay for Class IIa Histone Deacetylases. Issue 13 (30th January 2017) - Meyners, Christian; Mertens, Monique; Wessig, Pablo; Meyer‐Almes, Franz‐Josef
Abstract: Class IIa histone deacetylases (HDACs) show extremely low enzymatic activity and no commonly accepted endogenous substrate is known today. Increasing evidence suggests that these enzymes exert their effect rather through molecular recognition of acetylated proteins and recruiting other proteins like HDAC3 to the desired target location. Accordingly, class IIa HDACs like bromodomains have been suggested to act as "Readers" of acetyl marks, whereas enzymatically active HDACs of class I or IIb are called "Erasers" to highlight their capability to remove acetyl groups from acetylated histones or other proteins. Small‐molecule ligands of class IIa histone deacetylases (HDACs) have gained tremendous attention during the last decade and have been suggested as pharmaceutical targets in several indication areas such as cancer, Huntington's disease and muscular atrophy. Up to now, only enzyme activity assays with artificial chemically activated trifluoroacetylated substrates are in use for the identification and characterization of new active compounds against class IIa HDACs. Here, we describe the first binding assay for this class of HDAC enzymes that involves a simple mix‐and‐measure procedure and an extraordinarily robust fluorescence lifetime readout based on [1, 3]dioxolo[4, 5‐ f ]benzodioxole‐based ligand probes. The principle of the assay is generic and can also be transferred to class I HDAC8. Abstract : Screening for HDAC inhibitors : A generic competitive binding assay for class IIa histone deacetylases (HDACs) enables robust and high‐throughput compound screening. Displacement of the [1, 3]dioxolo[4, 5‐ f ]benzodioxole (DBD)‐ligand probe by an active substance is indicated by a dramatic change in fluorescence lifetime of up to 6 ns (see graphic).